Tendência de mortalidade infantil e mortalidade infantil evitável em municípios da região metropolitana de Porto Alegre/RS - Stahnke, Douglas Nunes (Universidade do Vale do Rio dos Sinos, 2023)
Introduction: Infant mortality (IM) is one of the United Nations (UN) millennium development goals and a guide for public health policies in Brazil. The Ministry of Health created a list of preventable diseases in children under five years of age that has been used to monitor the most prevalent diseases and the quality of the care network. With a prominent role in the care of pregnant women, postpartum women and newborns, the Family Health Strategy (FHS) has consolidated itself as a priority entry point into the services offered by the Unified Health System. Despite this, the complexity of care for this population can needing hospital care, which demands greater investment from government managers. Therefore, knowing the health situation in the region becomes essential to invest financial resources efficiently in order to improve the quality of care provided and achieve improvements in health indicators. Thus, the objectives of the present study were to describe and analyze the trend in infant mortality and preventable infant mortality (PIM) in the municipalities of the metropolitan region of Porto Alegre from 1996 to 2021 and its association with FHS coverage and per capita public spending in health. The objectives were also to describe and analyze the trend in preventable early (ENM) and late (LNM) neonatal mortality, stratifying deaths by groups and specific causes. Methods: Ecological time series study in the municipalities of Novo Hamburgo, São Leopoldo, Sapucaia do Sul, Esteio, Canoas and Porto Alegre. Data were obtained from the Mortality Information System, Live Birth Information System, Department of Primary Care and Public Health Budget System. Information on mortality was presented in coefficients, FHS coverage in percentage and expenditure on health in Reais, corrected by the Extended National Consumer Price Index. The trend analysis used the Prais-Winsten method and its results were expressed as increasing, decreasing and stationary. The association analysis considered results with a p value <0.05 to be significant. Results: in article 1, all municipalities showed a decreasing trend in IM. In PIM, only Esteio differed from the decrease, presenting a stationary trend. Per capita public spending on health was associated with IM and PIM in Novo Hamburgo, Canoas and Porto Alegre. FHS coverage was associated with IM and PIM in Novo Hamburgo, Canoas and Porto Alegre. In IM, this association was also found in Sapucaia do Sul. In article 2, both ENM and LNM showed a decreasing trend in Canoas and Porto Alegre. At ENM this trend also occurred in Novo Hamburgo. In the ENM, an increasing trend was found in the group of causes reducible by adequate care for women during pregnancy in São Leopoldo and Sapucaia do Sul. In the LNM, an increasing trend was found in the group of causes reducible by care for the newborn in Canoas. Newborn respiratory distress syndrome, neonatal infections other than congenital rubella syndrome and congenital viral hepatitis were the main specific causes of early and late neonatal deaths respectively, with a decreasing trend. Conclusions: Even though the reduction in IM and PIM is an important result, it may be necessary to continue increasing investments in health in view of their impacts verified in the present study. Even though FHS coverage has increased since its implementation, it is essential that the focus can be turned to policies that reach comprehensiveness and longitudinality of care, women during pregnancy and the postpartum period, as well as newborns, to reduce ENM and LNM aiming to meet global, national and regional targets for these indicators.
Keywords: Mortalidade infantil; Gastos públicos com saúde; Mortalidade neonatal; Estratégia saúde da família; Causas de mortes; Infant mortality; Public expenditures on health; Neonatal mortality; Family health strategy; Causes of death; ACCNPQ::Ciências da Saúde::Saúde Coletiva